The universalism and generosity of the lotus sutra: an emblematic reaction for a new world - Tola, Fernando (2009)
The date of the Parinirva of the Buddha. Early Buddhism There is not a general agreement about the date of the Parinirva of the Buddha. There are on this respect many opinions accepted by diverse Buddhist communities and by diverse scholars. Each one of these opinions is based in traditions, arguments and texts, according to which the date of the Parinirv25a should be located between the years 368 and 965 before the beginning of the Common Era. This fact indicates the importance of the divergences regarding the matter. The great symposium celebrated at Göttingen in the year 1988, on The Dating of the Historical Buddha (whose Proceedings were published1 in three volumes with a total of one thousand two hundred pages), reached no positive result. As a work hypothesis we fix for the Parinirva circa 480 before the C.E., and, as there is a general acceptance that the Buddha lived for 80 years, we fix the date of his birth circa 560 before the C.E. During great part of His life of 80 years the Buddha was dedicated to the preaching of his Doctrine. We can give the name of “Early Buddhism” to that form of Buddhism as taught by the Buddha himself. This form is recorded in many of the texts written in Pli included in the Pli Tipiaka